Social inequalities and psychosomatic complaints in Icelandic adolescents - Arnarsson, Ársæll Már (Menntavísindasvið Háskóla Íslands, 2020)
Adolescent well-being has been decreasing in most Western societies for the past decades. This is particularly true of girls. Better socioeconomic status (SES) has been shown to increase the likelihood of adolescents being happy, healthy and enjoying school. Studies have also shown that adolescents with lower SES are more likely to engage in risky behavior (e.g., smoking, having a poor diet or being sedentary), have a more negative view of their health and well-being, and have more problems regarding behavior, emotions and relations. Poor living conditions, whether caused by a difficult financial situation at home or social inequality, are a risk factor of adolescent health. The stress and strain of a low SES particularly affects the family life of these adolescents, causing worse communication, more conflict and lower support. All of these are known risk factors regarding adolescent health. Iceland is an interesting case in this respect. It is a highly prosperous society with some of the lowest levels of social inequalities measured in the OECD countries. It is, therefore, particularly interesting to see whether health inequalities exist among adolescents living in a country where material privation is rare and equality is high. The study is based on information gathered as part of the project Health Behaviour in School-Aged Children (HBSC) in which adolescents are asked about various issues related to health, well-being and social situation. Answers were collected from students in the 6th, 8th and 10th grade in consequent waves in 2006, 2010, 2014 and 2018. Prior to data collection the questionnaires, along with a research plan, were sent to the Icelandic Data Protection Authority and the University of Iceland Ethics Committee, neither of which had any reservations regarding the procedure. Then the same information was sent to all headmasters in Iceland in schools with students in the 6th, 8th or 10th grade, asking for their permission to run the study. Subsequently all parents and guardians received a letter ...